Effects of Two Different Dosages of Sildenafil on Patients With Erectile Dysfunction. (May 2017) - Li, Hongjun; Bai, Gang; Zhang, Xinyu; Shi, Bingbing; Liu, Defeng; Jiang, Hui; Ji, Zhigang; Davis, Matthew R.; Zhu, Ziwen; Fang, Yujiang
To investigate the effects of two different dosages of sildenafil on patients with erectile dysfunction (ED), a total of 3, 674 patients with ED were recruited to answer questionnaires designed specifically for this study. There were 977 patients in the 50 mg group and there were 2, 697 patients in the 100 mg group. Both 50 mg and 100 mg of sildenafil therapy increased the ED patients' average monthly frequency of sexual intercourse, improved erectile function state in self-assessment, and elevated sexual satisfaction and enjoyment. Despite a higher rate of concomitant diseases, patients in the higher dosage of sildenafil group had a better outcome in the average monthly frequency of sexual intercourse and sexual enjoyment compared with those in the lower dosage. Such a study might be helpful for health care providers to choose sildenafil dosage for patients with ED.